2016
DOI: 10.5051/jpis.2016.46.5.291
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of mineralized bone cortical allograft for immediate implant placement in extraction sites: anin vivostudy in dogs

Abstract: PurposeThe aim of the present study was to evaluate the effectiveness of using a mineralized bone cortical allograft (MBCA), with or without a resorbable collagenous membrane derived from bovine pericardium, on alveolar bone remodeling after immediate implant placement in a dog model.MethodsSix mongrel dogs were included. The test and control sites were randomly selected. Four biradicular premolars were extracted from the mandible. In control sites, implants without an allograft or membrane were placed immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It has been postulated that increased bone regeneration in the extraction socket should preserve the alveolar bone 49 . The canine tooth extraction socket has provided an ideal model to investigate the effectiveness of bone graft materials such as autograft 50 , decellularized allograft 51 , bovine decellularized xenograft 52 , and synthetic bone graft 53 . Using a published protocol 54 , a canine mandibular third premolar was hemisected and the distal root was extracted.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that increased bone regeneration in the extraction socket should preserve the alveolar bone 49 . The canine tooth extraction socket has provided an ideal model to investigate the effectiveness of bone graft materials such as autograft 50 , decellularized allograft 51 , bovine decellularized xenograft 52 , and synthetic bone graft 53 . Using a published protocol 54 , a canine mandibular third premolar was hemisected and the distal root was extracted.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Thus, the abilities of bone forming and resorption are important properties for bone materials. Orti et al 22 showed that the regenerated bone of allografts was similar to the original bone in terms of histological structure. Kubosch et al 19 reported that the expression of osteogenic biomarkers of human osteoblasts cultured on allograft and Bio-Oss were similar.…”
Section: Discussionmentioning
confidence: 96%
“…The maintenance of CBL in this study may be attributed to the surgical technique, which is characterized by the placement of mineralized FDBA granules into the gap and in excess over the buccal bone, followed by covering with a non-cross linked collagen membrane. Although this surgical technique has been used extensively in regenerative procedures [33,34], there is insufficient scientific evidence to support its efficacy in immediate implant placement [32,35].…”
Section: Discussionmentioning
confidence: 99%